Efficacy of herbicides, their effects on rice yield under saturated soil condition - Abdullah, Mohd Razif; Ahmad Hamdani, Muhammad Saiful; Zakaria, Norazua; Karim, SM Rezaul (Bangladesh Botanical Society, 2023)
This study was carried out in containers which were placed outdoor to evaluate the efficacy of different herbicides with different mixtures on weed growth suppression in rice and their effects on rice grain yield under saturated soil water regime in two consecutive seasons (cropping season and off season) at the Universiti Putra Malaysia Farm, Serdang, Selangor, Malaysia during 2016 to 2017. Eight combinations of different herbicides, viz. T1, T2, T3, T4, T5, T6, T7 and T8 along with weed free and non-weeded treatments were used in the study following a RCBD. Weed composition in the experimental containers and their summed dominant ratio (SDR) at 60 days after planting were recorded from non-treated containers. Naturally grown eleven weed species mainly under the families of Poaceae, Cyperaceae and Pontederiaceae were found in the experimental containers. Based on the SDR values the dominant weed species were Monochoria vaginalis, Echinochloa crus-galli, and Fimbristylis miliacea in both the seasons. Results revealed that four herbicide treatments viz. Pretilachor fb Bentazon/MCPA (T1), Pretilachor+Pyribenzoxim fb Bentazon/MCPA (T2). Bispyribac-sodium fb Bentazon/MCPA (T2), Fenoxaprop+Ethoxysulfuron (T3), fb Bentazon/MCPA (T7) were superior in their effectiveness for weed control in both seasons and gave better rice grain yield with high economic return.